Efeitos da fotobiomodulação intra operatória nos pedículos de retalhos cutâneos de camundongos - Chang, Alexandre Jin Bok Audi (2021)
The loss of skin flaps (CR) due to tissue necrosis can be catastrophic and may potentially cause death. This outcome occurs between 2 to 20% of the procedures performed. The main cause is tissue hypoperfusion combined with ischemia-reperfusion injury. Currently, there is no adjuvant treatment that improves skin flaps survival, without side effects or risks. Recent studies seek to prove the efficiency of Low Level Laser Therapy (LLLT), as an adjuvant therapy, and show promising results for increasing the survival of CRs. The objective of this study was to evaluate the effect of fotobiomodulação on dorsal skin flaps in mice. In this study we used 48 adult male mice (Balb / C, 20 - 25g), divided into two groups: Control (n = 24) and Experiment (n = 24). Skin flaps were raised on the backs of animals in both groups and submitted the flaps to low-level laser irradiation in the Experiment group. In the Control group, there was only a simulation of the application. The LLLT was applied at the internal pedicle of the flap with a wavelength of 660 nm, radiant exposure of 2 J / cm2 for a total time of 20 seconds in the interior base of the flap as a scan passage, within the flap vascular pedicle. After treatment, animals were separated into 3 subgroups (according to the day of euthanasia) containing 8 animals each Control and Experimental groups. The animals were euthanized on the 4th, 7th and 10th postoperative days. We analyzed the percentage of tissue necrosis in the flaps, such as interleukin levels 1 (IL-1), 6 (IL-6), 10 (IL-10) and the Tumor Necrosis Factor (TNF-alpha). In addition, flap histological analysis was performed to assess the number of inflammatory cells and the degree of ischemic tissue destruction. The results were that LLLT reduced the flaps distal necrosis, significantly decreased cytokines IL-1, IL-6, TNF-α, inflammatory cells, the degree of tissue destruction and increase the anti inflammatory cytokine IL-10 in the LLLT groups compared to Control groups. LLLT can improve skin flap survival by decreasing inflammation, both by reducing inflammatory cells and inflammatory cytokines and by increasing an endogenous anti-inflammatory cytokine, IL-10.